High-speed, low-cost, pulsed laser diode based second generation desktop photoacoustic tomography system - Kalva, Sandeep Kumar (2018)
Bulky, expensive Nd:YAG lasers are used in conventional photoacoustic tomography (PAT) systems making them difficult to translate into clinics. Moreover, real-time imaging is not feasible when single-element ultrasound transducer is used with these low pulse repetition rate lasers (10-100 Hz). Low-cost pulsed laser diodes (PLD) can be used instead for photoacoustic imaging due to their high pulse repetition rates and compact size. Together with acoustic reflector based multiple single element ultrasound transducers portable desktop PAT system was developed. This second generation pulsed laser diode based photoacoustic tomography (PLD-PAT-G2) achieved 0.5 s cross-sectional imaging time with a high spatial resolution of ~165 m and an imaging depth of 3 cm. The performance of this system was characterized using phantom and in vivo studies. Dynamic in vivo imaging was also demonstrated by monitoring the fast uptake and clearance of indocyanine green in small animal (rat) brain vasculature.